Exploring Load Balancing in Heterogeneous Networks by Rate Distribution - Louha, K.; Jun, J.H.; Agrawal, D.P. (2008 IEEE International Performance, Computing and Communications Conference, 2008)
We present a mechanism for optimum distribution of internet traffic over heterogeneous network environment. A heterogeneous network can be considered as a combination of multiple homogenous networks available simultaneously to the end users. For simplicity, each network has been modeled as a M/M/1 queue. We aim to minimize the number of jobs in each queue subject to constraints. The optimization problem has been achieved through the use of Lagrange multiplier. Depending on their service rate the formulation done in this work is shown to optimally divide the rate of incoming traffic into different networks.